2023
DOI: 10.1021/acs.jpcb.3c00613
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Comparison of Single- and Multiple-Macrostate Grand Canonical Ensemble Transition-Matrix Monte Carlo Simulations

Abstract: Recent interest in parallelizing flat-histogram transition-matrix Monte Carlo simulations in the grand canonical ensemble, due to its demonstrated effectiveness in studying phase behavior, self-assembly and adsorption, has led to the most extreme case of single-macrostate simulations, where each macrostate is simulated independently with ghost particle insertions and deletions. Despite their use in several studies, no efficiency comparisons of these single-macrostate simulations have been made with multiple-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The second move is another canonical move, based on an extension of the AVBMC3 move, which we label AVBMC4. A full description of this AVB move is given in ref and described in Section SI.3 of the SI but may be summarized as a move that selects two target, nonbonded SPC/E molecules and then attempts to move a third bonded molecule from one target molecule to the other. The AVB GC transfer move is simply a GC transfer move that preferentially inserts (deletes) an SPC/E molecule in (from) the bonded region of a target molecule .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second move is another canonical move, based on an extension of the AVBMC3 move, which we label AVBMC4. A full description of this AVB move is given in ref and described in Section SI.3 of the SI but may be summarized as a move that selects two target, nonbonded SPC/E molecules and then attempts to move a third bonded molecule from one target molecule to the other. The AVB GC transfer move is simply a GC transfer move that preferentially inserts (deletes) an SPC/E molecule in (from) the bonded region of a target molecule .…”
Section: Methodsmentioning
confidence: 99%
“…The chemical potentials were chosen to yield local maxima in ln Π(N;μ) that aid explanatory discussion. The macrostate domains were divided into windows using an exponential strategy, 43 with exponent 1.5, 48 windows for CO 2 , and 80 windows for SPC/E water (roughly the same number of windows relative to N max ). The simplest MC move set was used (unbiased translations, rotations, and GC transfer moves, with relative weights 3:2:5) and no lookup tables or cell lists were utilized to speed up calculations for the preliminary simulations; this is a basic implementation of TMMC in FEASST.…”
Section: Simulation and Molecular Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the total number of molecules remains constant through simulation. Hatch et al 46 demonstrated that single-macrostate simulations are less efficient than multiple-macrostate simulations, mainly due to the lack of microstate sampling. However, we show that with single-macrostate simulations, it is possible to skip sampling certain macrostates and interpolate transition probabilities to obtain the full MPD with reduced simulation cost.…”
Section: Methodsmentioning
confidence: 99%